Chronic urticaria as a manifestation of multicentric Castleman disease treated with rituximab - Osorio‐Aragón I. Yolanda; Milián‐Solís Ximena; Berumen‐Glinz Cristina; Vargas C. Estefanía; Vega‐Memije M. Elisa; Andrade‐Rojas J. Jose; Contreras‐Solis M. Fernanda; González‐Hernández Isaac (Wiley, 2024)
Abstract We present the case of a 26‐year‐old female with chronic urticaria (CU) with systemic symptoms in whom comprehensive laboratory and imaging studies led to the diagnosis of idiopathic multicentric Castleman disease. Treatment with rituximab induced resolution of CU. The association between these two entities is rare, and common autoimmune and autoinflammatory pathways may be involved in their production. Our case also emphasized the association of CU with an underlying systemic disease.